The effects of dance on maternal childbirth: a systematic review and meta-analysis - Luping Zhang; Ru Yue; Feng Xiao; Fulan Wang; Zhiwei Zhang (BMC Pregnancy and Childbirth)
Abstract Background Previous guidelines have clearly stated that dance is safe and beneficial during pregnancy and for childbirth. However, due to the small sample size of individual studies and different interventions, there were inconsistencies about the effect of dance on maternal childbirth. Methods We included studies evaluating the effect of dance on women in labor. Risk of bias was assessed using the revised Risk of bias assessment tool for randomized controlled trials (RCTs). Data analyses was performed using Review Manager Software version 5.4. Results A total of 12 RCTs comprising 1,486 pregnant women were included in the analysis. We found that the rate of natural childbirth and satisfaction with delivery were higher in the dance group than in the control group.The pain at 30 min and at 60 min after the intervention were lower in the dance group than in the control group. Meanwhile, the duration of the first stage, the second stage and the total labor duration was shorter in the dance group than in the control group.However, there were no statistically significant differences in the pain at 90 min after intervention, the duration of the third stage, and the rate of the normal 1-minute Apgar scores > 7 points between the two groups. Conclusions Dance during labor could reduce labor pain to an extent, shorten the duration of labor, promote natural childbirth, and improve satisfaction with labor, with no adverse effects on neonatal outcomes. Trial registration The protocol for this review was prospectively registered in the international prospective register of systematic reviews (PROSPERO) under the registration number CRD42022351001.